Perbandingan Aktivitas Antibiofilm Ekstrak Biji Kopi Hijau dan Sangrai Kopi Robusta terhadap Staphylococcus aureus - Urip, Sri Khanti; Wardani, Tatiana Siska; Listyani, Tiara Ajeng (Publikasi Penelitian Terapan dan Kebijakan, 2023)
Green Coffee Beans (Coffea canephora P.) and Roasted Robusta Coffee (Coffea canephora L.) contain compounds including caffeine, polyphenols, flavonoids, chlorogenic acid. Chlorogenic acid is a phenolic compound contained in coffee beans which functions as an antifungal and antibacterial. Some infectious diseases caused by Staphylococcus aureus are boils, acne and wound infections and have the ability to inhibit biofilm. Biofilms are aggregates of microorganisms covered by an extracellular polymer matrix produced by microorganisms. This study aims to test the antibiofilm inhibition and destruction of green coffee bean extract (Coffea canephora P.) and roasted robusta coffee (Coffea canephora L.) against Staphylococcus aureus ATCC 25923. The antibiofilm activity test consists of a biofilm formation test, a biofilm inhibition test, and a destruction of biofilm using the Microtitter Plate Biofilm Assay method on extract samples macerated with 96% ethanol. The antibiofilm activity test used concentrations of 2, 4.8, 16 mg/mL. The results of testing the antibiofilm activity of green coffee bean extract and roasted robusta coffee had inhibitory activity with calculated IC50 values of 4.14 mg/mL and 2.13 mg/mL. The results of the crushing activity of green coffee bean extract and roasted robusta coffee with calculated EC50 values were 10.18 mg/mL and 19.32 mg/mL.